DEVELOPMENT OF PROCESSING TECHNOLOGIES FOR INTENSIVE DEVELOPMENT OF HORSE BREEDING - Iskhan Kairat Zhaleluly (Academic Journal of Physical and Chemical Sciences, 2020)
The optimal parameters of the dairy productivity of female horses of the Kazakh Jabe horses and Kushum breed were determined depending on the technological parameters of the udder (cup-shaped, round, goat). So, mares with a cup-shaped udder reliably surpass peers with a round and goat udder. The mares of the Kazakh horse of Jabe type with a cup-shaped udder are superior in average daily milk yield to individuals with a round udder in 23.8%, with goat udder - 71.2%. A similar picture is observed in mares of the Kushum breed, the difference between the cup-shaped and round forms of the udder is 16.4%, the cup-shaped and goat - 57.1%. In fat content, no significant difference was found. The fat content in milk in the third month of lactation was 1.37-1.38% in Jabe mares, 1.32-1.33% in the Kushum breed. The full value degree of lactation is pronounced in all mares with the cup-shaped udder, in comparison with round and goat forms. Jabe mares with a cup-shaped udder reliably exceed their peers with round udder in terms of the full value of lactation by 6.3% in absolute terms, mares with goat udder - by 16.1% in absolute terms. Mares of Kushum breed with the cup-shaped udder reliably exceed their peers with round udder by 5.7%, with goat udder by 21.2%. Female horses of the Kazakh Jabe horses with the cup-shaped udder, nipple length of at least 2.5 cm, milk yield of at least 7.1 kg in the third month of lactation are preferred for targeted breeding and selection for dairy productivity. Mares of Kushum breed with the cup-shaped udder, flat-shaped nipples directed vertically downward, nipple length not less than 3.0 cm and not more than 6.0 cm, milk yield not less than 9.5 kg in the third month of lactation are desirable for targeted breeding and selection for dairy productivity. It was established that in the preweaning period, the average daily gain in stallions is 1511-690-482 g, in mares 1496-675-472 g. In the post-dairy period, the average daily gain is significantly reduced in stallions - 406-882 g, in mares - 377-842g. It was found that in mares with the cup-shaped udder, due to higher milking capacity, foals grow better and have higher average daily gain.